INFLUENCE OF TELEVISION BROADCASTS ON VOTERS’ CHOICE OF PARTIES: A STUDY OF 2007 NIGERIAN PRESIDENTIAL ELECTION - Aririguzoh, Stella A. (University of Nigeria Journal of Political Economy, 2022)
Because of televisions’ wide popularity, political parties and their contestants have used it to reach and deliver various messages to a large number of people in order to advertise and promote themselves. Since television wields influence, these political institutions believe that canvassing from this podium would confer on them added advantages, especially making the voters to favour their points of opinion and consequently cast their votes for them. It is therefore nothing to be wondered at that politicians have vigorously engaged this medium to reach out to voters and to those who are sympathetic to their causes. They believe that a relationship exists between their appearances on television and electoral outcomes. Those campaigning for public offices assume television broadcasts influences the manner in which members of the electorates vote. This study sought to find out if the various pieces of broadcasts from television on the 2007 Nigerian presidential election influenced the choices of political parties that voters in Ado Odo/Ota made. When the various variables were subjected to statistical tests significant and positive relationships were found among all the variables testing to see if the respondents’ exposure to television influenced their choices of the political parties that they voted for. It was discovered that indeed television broadcasts influenced these choices. Because the value were low, it was also found that there were some other underlying factors like partisanship, that also influenced the choice of the voters.